Temperature Growth Response of Spoilage Bacteria Isolated from Indian Oil Sardine (Sardinella longiceps) Stored in Chilled Sea Water - T. S., Shetty; T.M.R., Setty; C.N., Ravishankar (Fishery Technology, 2025)
The optimum growth temperature of different bacterial genera, important in the spoilage f Indian oil sardine (Sardinella longiceps)stored in chilled sea water was studied. Isolates belonging to different bacterial genera, selected from plates incubated at 28 ± 2°C and 2 ± 1°C, were tested for their growth response at different temperatures. The results indicated hat the spoilage bacteria, irrespective of their primary isolation temperatures, showed good growth response only at the temperature ranging from 2 ± 1°C to 28 ± 1°C, indicating heir facultative psychrophilic nature.